2023
DOI: 10.3390/agronomy13010155
|View full text |Cite
|
Sign up to set email alerts
|

Spring Wheat–Summer Maize Annual Crop System Grain Yield and Nitrogen Utilization Response to Nitrogen Application Rate in the Thermal–Resource–Limited Region of the North China Plain

Abstract: Spring wheat–summer maize (SWSM) annual crop systems were formed to satisfy the maize grain mechanized harvest thermal requirement in the thermal–resource–limited region of the North China Plain. However, the nitrogen (N) application rate effect on SWSM annual yield formation, N accumulation and utilization were barely evaluated. Two–year field experiments were conducted to evaluate the effects of the N application rate on the annual yield of SWSM, observe N accumulation and utilization, and identify the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…Nitrogen is one of the essential elements of crops, which contributes 40-50% to yield [17]. The grain yield tends to increase with the fertilizer rate within limits, while at high fertilizer levels, excessive vegetative growth and serious lodging may be responsible for yield loss [18,19]. The results in this study indicated that the yield of foxtail millet increased first and then decreased with the increase in nitrogen application rate (Table 1), which is in agreement with the results of previous studies [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen is one of the essential elements of crops, which contributes 40-50% to yield [17]. The grain yield tends to increase with the fertilizer rate within limits, while at high fertilizer levels, excessive vegetative growth and serious lodging may be responsible for yield loss [18,19]. The results in this study indicated that the yield of foxtail millet increased first and then decreased with the increase in nitrogen application rate (Table 1), which is in agreement with the results of previous studies [20].…”
Section: Discussionmentioning
confidence: 99%